Performance Openness in Contemporary Ceramic Formation - Hadi AbbasMukheef; Saad Hafez Obaid; Hussein Ali Farhan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The research problem marked (operative openness in contemporary ceramic formation) dealt with the nature of the performative openness and the technical expansion to produce contemporary artworks, and the nature of the materials taken as components of their sensory structure, and the research came from four sections: the general framework of the research and the research problem and the need for it were identified with an indication of the importance of its existence. And then defining the goal of the research represented in defining the performative openness in contemporary ceramic formation, followed by laying the three research boundaries (objective, temporal and spatial) after which, then defining the terms related to the title. Then presenting the theoretical framework and indicators that resulted from academic theorizing of the topic. The researchers have identified two implicit titles within this framework to ensure that the research topic is read in accordance with its various definitional frameworks. The first topic is the concept of performance openness and the second topic is the scenery of performance openness in contemporary ceramics. As for the third chapter only for the research procedures, by revealing the studied community and the selected sample from (3 works), then determining the methodological research tool, followed by the sample analysis. The fourth chapter included the research results, conclusions and recommendations from them.